2003
DOI: 10.1189/jlb.1002479
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in shear stress, activation of the endothelium, and leukocyte priming are all required for leukocyte passage across the blood—retina barrier

Abstract: The passage of leukocytes across the blood-retina barrier at the early stages of an inflammatory reaction is influenced by a complex series of interactions about which little is known. In particular, the relationship between hydrodynamic factors, such as shear stress and leukocyte velocity, to the adherence and subsequent extravasation of leukocytes into the retina is unclear. We have used a physiological method, scanning laser ophthalmoscopy, to track labeled leukocytes circulating in the retina, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 25 publications
1
40
0
1
Order By: Relevance
“…Histological examination has shown that inflammatory cell infiltration and perivasculitis occur at day 9 pi, with infiltrating cells distributed in the ganglion layer and vitreous. Most of the photoreceptor layer remains normal at this time, but there is some focal photoreceptor cell damage (34). No rolling of Ag-primed leukocytes is seen before day 9 pi EAU (34).…”
Section: Induction Of Eaumentioning
confidence: 99%
See 2 more Smart Citations
“…Histological examination has shown that inflammatory cell infiltration and perivasculitis occur at day 9 pi, with infiltrating cells distributed in the ganglion layer and vitreous. Most of the photoreceptor layer remains normal at this time, but there is some focal photoreceptor cell damage (34). No rolling of Ag-primed leukocytes is seen before day 9 pi EAU (34).…”
Section: Induction Of Eaumentioning
confidence: 99%
“…Most of the photoreceptor layer remains normal at this time, but there is some focal photoreceptor cell damage (34). No rolling of Ag-primed leukocytes is seen before day 9 pi EAU (34).…”
Section: Induction Of Eaumentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed recent work suggests that shear stress may be the most critical factor affecting gene expression in endothelial cells and during inflammation. Data from in vitro (Stone et al, 2003;Walsh et al;Warabi et al, 2004) and in vivo (Xu et al, 2004;Yamawaki et al, 2003) studies indicate that low or low oscillating endothelial shear stress upregulates molecular and vascular responses that may be instrumental to progression of vascular-related diseases. Excessive erythrocytosis compromises vascular homeostasis as a result of significantly increased hematocrit and decreased plasma levels (Neunteufl et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial cells are constantly subjected to shear stress imposed on them by blood flow, and shear stress may be a critical factor affecting gene expression in endothelial cells during inflammation. Data from in vitro (42) and in vivo (49,50) studies indicate that low or low-oscillating endothelial shear stress induces molecular and vascular responses that may be instrumental in progression of vascular-related diseases (47). Because shear stress is a function of blood viscosity, blood flow velocity, and vessel diameter, it is very difficult to assess this parameter in capillaries of tg6 mice.…”
Section: Discussionmentioning
confidence: 99%